PELAKSANAAN PERATURAN MENTERI KESEHATAN NOMOR 1871/MENKES/PER/IX/2011 TENTANG PENCABUTAN PERATURAN MENTERI KESEHATAN NOMOR 339/MENKES/PER/V/1989 TENTANG PEKERJAAN TUKANG GIGI - Adiani, Ni Wayan; Wairocana, I Gusti Ngurah (Kertha Negara : Journal Ilmu Hukum, 2013)
The article is entitled "Ministry of Health Regulation Number 1871/MENKESs/PER/IX/2011 regarding the Revocation of Ministry of Health Regulation Number 339/MENKES/PER/V/1989 regarding Dental Handyman". This article utilizes normative analysis method combined with legislative approach and factual approach. Needs of dental healthcare had been consequently increasing along with the increasing demand of the related healthcare services itself. One of the contributing dental health care agents in society shall be the Dental Handyman. Its existence due to the enactment of Ministry of Health Regulation Number No. 1871/MENKES/PER/IX/2011 remain a controversy. The regulation basically explains that after the disclosure or after certain dental handyman license expires, they shall no longer be able to operate. Formulation of the problem shall be observed is the implementation of Ministry of Health Regulation Number 1871/2011 along with its correlating factors. The results and conclusions obtained namely that Permenkes No. 1871/MENKES/PER/IX/2011 is not yet implemented due to several factors, among other factors shall be the law, the law enforcing factor, availability of facility or means, society factors and cultural factors.
Keywords: Implementation, Dental Handyman, Dental Care, License